Investigation of the Stage Performance and Flow Fields in a Centrifugal Compressor with a Vaneless Diffuser - Ahti Jaatinen-Värri; Aki Grönman; Teemu Turunen-Saaresti; Jari Backman (International Journal of Rotating Machinery)
The effect of the width of the vaneless diffuser on the stage performance and flow fields of a centrifugal compressor is studied numerically and experimentally. The diffuser width is varied by reducing the diffuser flow area from the shroud side (i.e., pinching the diffuser). Seven different diffuser widths are studied with numerical simulation. In the modeling, the diffuser width b/b2 is varied within the range 1.00 to 0.50. The numerical results are compared with results obtained in previous studies. In addition, two of the diffusers are further investigated with experimental measurement. The main finding of the work is that the pinch reduces losses in the impeller associated with the tip-clearance flow. Furthermore, it is shown that a too large width reduction causes the flow to accelerate excessively, resulting in a highly nonuniform flow field and flow separation near the shroud.